2016
DOI: 10.1111/jmft.12197
|View full text |Cite
|
Sign up to set email alerts
|

Are we there yet? Faculty Members’ Beliefs and Teaching Practices Related to the Ethical Treatment of Lesbian, Gay, and Bisexual Clients

Abstract: The purpose of this study was to explore (a) faculty members' beliefs about the ethics of reparative therapy and referring lesbian, gay, and bisexual (LGB) clients, (b) course content related to reparative therapy and referral of LGB clients, and (c) positions taken by programs associated with reparative therapy and referral of LGB clients. A total of 117 faculty members from accredited family therapy programs completed an online survey for this study. While the vast majority of faculty members reported that r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
5
0
5
Order By: Relevance
“…Counter to the religious justification for conversion therapy found in previous literature (Arthur et al, 2014;McGeorge et al, 2017), the participants in this study appear to believe that the practice of conversion therapy is a misuse of religion. The pastors interviewed for this study repeatedly stated that based on the primary teachings of their faith, there is nothing about LGB people that needs to be fixed or altered, because God created and loves LGB people just as they are.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Counter to the religious justification for conversion therapy found in previous literature (Arthur et al, 2014;McGeorge et al, 2017), the participants in this study appear to believe that the practice of conversion therapy is a misuse of religion. The pastors interviewed for this study repeatedly stated that based on the primary teachings of their faith, there is nothing about LGB people that needs to be fixed or altered, because God created and loves LGB people just as they are.…”
Section: Discussionmentioning
confidence: 55%
“…This belief that conversion therapy is harmful and should not be practiced mirrors the secular scholarly literature on conversion therapy (Bradshaw et al, 2015; Dehlin et al, 2015; Haldeman, 2002; Shidlo & Schroeder, 2002). Moreover none of the participants provided justification for the need for conversion therapy, diverting from the opinions of those who engage in this practice and some family therapy faculty (Arthur et al, 2014; Cyphers, 2014; McGeorge et al, 2017). For example, one study found that although the majority of family therapy faculty members surveyed perceived conversion therapy to be unethical, there was a sub‐group of faculty who argued that conversion therapy was ethical based on client autonomy and compliance with religious beliefs (McGeorge et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Os aspectos gerais dos estudos (Figura 3.2) representam a síntese de cada um dos quatro artigos, por meio das seguintes categorias: 1. autor, ano e país de origem; 2. tamanho da amostra; 3. delineamento do estudo; 4. periódico, Qualis e/ ou fator de impacto; 5. instrumentos; e 6. resultados. Das quatro publicações selecionadas para análise, uma é de origem nacional (Vezzosi, Ramos, Segundo, & Costa, 2020), outras duas provenientes dos Estados Unidos (McGeorge, Carlson, & Maier, 2017;McGeorge, Carlson, & Toomey, 2015), e uma última originada na Itália (Lingiardi, Nardelli, & Tripodi, 2015). Os artigos de origem norte-americana -embora com autores e anos de publicação distintos -possuem publicações no mesmo Terapia reparativa: uma revisão sistemática periódico (McGeorge et al, 2015(McGeorge et al, , 2017.…”
Section: Resultsunclassified
“…Das quatro publicações selecionadas para análise, uma é de origem nacional (Vezzosi, Ramos, Segundo, & Costa, 2020), outras duas provenientes dos Estados Unidos (McGeorge, Carlson, & Maier, 2017;McGeorge, Carlson, & Toomey, 2015), e uma última originada na Itália (Lingiardi, Nardelli, & Tripodi, 2015). Os artigos de origem norte-americana -embora com autores e anos de publicação distintos -possuem publicações no mesmo Terapia reparativa: uma revisão sistemática periódico (McGeorge et al, 2015(McGeorge et al, , 2017. Quanto ao artigo proveniente da Itália, os dados apontam que ele -dentre os selecionados -apresenta o maior número de amostra de psicólogos/as (Lingiardi et al, 2015).…”
Section: Resultsunclassified